2005
DOI: 10.1159/000085840
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Steroid Excretion Rates in Acromegaly

Abstract: Using gas chromatography/mass spectrometry, urinary excretion rates of cortisol, cortisone and of various steroid metabolites were determined in 35 acromegalic patients (18 men, 17 women) and in 45 age- and weight-matched controls. The ratio of excreted cortisol/cortisone was similar in acromegalics (0.75 ± 0.20) and in controls (0.75 ± 0.24). Hence, the preponderance of the main cortisone-derived metabolite, tetrahydrocortisone, over the main metabolites of cortisol (tetrahydrocortisol and allotetrahydrocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…The low urine androsterone/etiocholanolone ratio identified in men with acromegaly demonstrated a decreased hepatic 5 α-reductase activity. 46 The inhibitory effect of GH on 11β-HSD1 was also observed by other researchers. 59,60…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The low urine androsterone/etiocholanolone ratio identified in men with acromegaly demonstrated a decreased hepatic 5 α-reductase activity. 46 The inhibitory effect of GH on 11β-HSD1 was also observed by other researchers. 59,60…”
Section: Discussionsupporting
confidence: 70%
“…Women with active acromegaly had low urinary glucocorticoids concentrations vs healthy women (p<0.001). 46 Men with active acromegaly had a decreased urinary androsterone/etiocholanolone ratio and an increased urinary tetrahydrocortisone/tetrahydrocortisol ratio vs healthy men (Table 1). 46 The androsterone/etiocholanolone ratio negatively correlated with IGF-1 (r = −0.4, p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11βHSD-1 activity has been shown to be inhibited by GH excess, resulting in the reduced tissue exposure to glucocorticoids [15,18]. In fact, it has been reported that the ratio of urinary tetrahydrocortisol (THF)+allo-THF to tetrahydrocortisone (THE) was reduced in acromegalic patients, suggesting the increased metabolic clearance of cortisol [19]. In addition, a rare case of Cushing's disease without the classical phenotype has been reported due to a partial defect in the 11βHSD-1 activity protective against cortisol excess [20].…”
Section: Discussionmentioning
confidence: 99%
“…Female rodents have lower hepatic 11βHSD1 enzyme activity than male animals (5). This putative gender difference in glucocorticoid metabolism may be influenced by sex hormones, growth hormones, and “adipokines,” i.e., fat‐derived hormones, including leptin and tumor necrosis factor‐alpha (TNF‐α), with a possible fat‐liver cross‐talk (6, 7, 8). However, little is known about potential influences of gender and adipokines on hepatic 11β reduction of cortisone in humans.…”
Section: Introductionmentioning
confidence: 99%